Origin and age of the earliest Martian crust from meteorite NWA 7533 - Humayun, M.; Nemchin, Alexander; Zanda, B.; Hewins, R.; Grange, Marion; Kennedy, Allen; Lorand, J.; Gopel, C.; Fieni, C.; Pont, S.; Deldicque, D. (Nature Publishing Group, 2013)
The ancient cratered terrain of the southern highlands of Mars is thought to hold clues to the planet’s early differentiation [1,2] but until now no meteoritic regolith breccias have been recovered from Mars. Here we show that the meteorite Northwest Africa (NWA) 7533 (paired with meteorite NWA 7034 [3]) is a polymict breccia consisting of a fine-grained interclast matrix containing clasts of igneous-textured rocks and fine-grained clast-laden impact melt rocks. High abundances of meteoritic siderophiles (for example nickel and iridium) found throughout the rock reach a level in the fine-grained portions equivalent to 5 per cent CI chondritic input, which is comparable to the highest levels found in lunar breccias. Furthermore, analyses of three leucocratic monzonite clasts show a correlation between nickel, iridium and magnesium consistent with differentiation from impact melts. Compositionally, all the fine-grained material is alkalic basalt, chemically identical (except for sulphur, chlorine and zinc) to soils from Gusev crater. Thus, we propose that NWA 7533 is a Martian regolith breccia. It contains zircons for which we measured an age of 4,428 ± 25 million years, which were later disturbed 1,712 ± 85 million years ago. This evidence for early crustal differentiation implies that the Martian crust, and its volatile inventory [4] formed in about the first 100 million years of Martian history, coeval with earliest crust formation on the Moon [5] and the Earth [6]. In addition, incompatible element abundances in clast-laden impact melt rocks and interclast matrix provide a geochemical estimate of the average thickness of the Martian crust (50 kilometres) comparable to that estimated geophysically [2,7].